Adoção de governo eletrônico no Brasil: a perspectiva do usuário do Programa Nota Fiscal Paulista - Moraes, Gustavo Hermínio Salati Marcondes de (2013)
The intensive use of information technology (IT) for all sectors has spread also in Public Administration. The use of IT coupled with the internet as a tool of public management is termed electronic government and aims to further qualify the provision of services to citizens and enable more effective participation in the political process. The present study aimed to investigate the context of electronic government in Brazil and presents a model of adoption based on an initiative of computerization of fiscal control mechanisms of São Paulo state. The overall aim of the thesis was to study what are the elements that affect the use of e-government in Brazil, through a study in the program Nota Fiscal Paulista (NFP). The methodology involved techniques of qualitative methods by the use of expert opinion, associated with quantitative method, through a survey applied to 715 users of the NFP. The analysis used structural equation modeling. The results contribute to the IT research, presenting a model that reinforces and extends previous studies on technology adoption and e-government studies and adding a model in a new context still little explored. In the case of NFP, the factors tested and that influence the adoption process are: Perceived Benefit, Perceived Ease of Use, Social Influence, Perceived Safety, Reliability and Habit. In practical terms, the research helps in understanding the participation and involvement of citizens in the current phase of development of e-government in Brazil. With better understanding of the influence of this technology in their personal and professional users, it is possible to raise the quality of service delivery to meet the demands of society. Thus, also helps in faster deployment of the program in other administrative contexts for e-government, generating useful information for key points to consider extending the accession of the people and having more chance of successful implementation.